(untitled) (International journal of artificial intelligence, 2026)
This scientific article examinesthe issues of integrating the Montessori method with innovatie technologies in the system of preschool education.The study analyzes the theoretical foundations of the Montessori method, its impact on thedevelopment of cognitiveactivity, independence, andcreativethinking of preschool children , as well as the possibilities of using modern digital technologies in the educational process. Special attention is paid to innovative approaches to combining the traditional Montessori environment wuth digital didactic resources.The research findings demonstrate that the integration of the Montessori method and innovative technologies contributes to improving the quality of the preschool education and the formation of key competencies in children.